Search for truth - Khan, Saniyasnain (GOODWORD BOOKS India, 2022)
Search for Truth is a compelling exploration of the quest for knowledge and understanding, guiding readers through philosophical reflections and life lessons that inspire a deeper appreciation for honesty and authenticity.